PENGARUH PEMBERIAN EDUKASI TERHADAP TINGKAT PENGETAHUAN PENGGUNAAN ANTIBIOTIK PADA PASIEN RAWAT JALAN RSUD Dr. MOEWARDI TAHUN 2023 - Magdalena Retnoningsih; Jason Merari Peranginangin; Nur Anggreini Dwi Sasangka (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2024)
Antibiotics are drugs to fight bacterial infections. Based on the large amount of antibiotic use, WHO states that the amount of irrational antibiotic use is relatively high, causing the risk of increasing resistance. This research was conducted to determine the level of patient knowledge about the use of antibiotics before and after being given education. This research used a pre-experiment design with one group pre-test and post-test with measuring instruments in the form of questionnaires. The number of samples used was 306 respondents, sample data was collected using purposive sampling by providing verbal education and leaflet media. Data analysis to determine the description of respondents based on characteristic criteria uses univariate analysis, to determine the relationship between respondent characteristics and level of knowledge using bivariate analysis, while to determine the influence between the independent variable and the dependent variable using statistical analysis the Wilcoxon difference test. The results of this research show that the level of knowledge at pre-test was 31% with high knowledge, 30.7% with moderate knowledge, 38.2% with low knowledge. In the post-test 99% had high knowledge, 0.7% had medium knowledge, 0.3% had low knowledge. The results obtained were tested using the Wilcoxon test which obtained a significance value of 0.000 < 0.05. From these results it can be concluded that there is an influence of providing education on the level of knowledge of outpatients at Dr. RSUD. Moewardi, and there is a significant relationship between the characteristics of respondents and the level of knowledge, p value <0.05.